PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN METODE HANDS-ON LEARNING PADA MATERI POLA GAMBAR DAN POLA BILANGAN DI KELAS IV SEKOLAH DASAR - Amalia, Annisa; Hariandi, Ahmad; Faisal Hidayat, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of implementing a problem-solving learning model with the hands-on learning method on students' problem-solving abilities in mathematics lessons on picture patterns and number patterns for fourth-grade students at SDN 194/I Sungai Abang. The study used a quantitative approach with a quasi-experimental design using a one-group pretest-posttest design. The subjects were 32 fourth-grade students at SDN 194/I Sungai Abang, selected using a saturated sampling technique. The research instrument was a mathematical problem-solving ability test on picture patterns and number patterns, which had been tested for validity and reliability. Data were analyzed using paired t-test statistics to determine differences in problem-solving abilities before and after implementing the problem-solving model with the hands-on learning method. The results showed a significant t-test gain score of 0.001 <0.05, indicating a significant difference in problem-solving abilities between the two classes. Thus, the application of the problem-solving learning model with the hands-on learning method significantly impacts students' problem-solving abilities. Thus, it can be concluded that the application of the problem-solving model combined with the hands-on learning method effectively improves students' mathematical problem-solving skills in the subject of picture patterns and number patterns in fourth-grade students at SDN 194/I Sungai Abang. Keywords: problem solving, hands-on learning, picture patterns and number patterns